2012
DOI: 10.1371/journal.pone.0039434
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Neurophysiologic and Neurocognitive Biomarkers for Use in Genomic and Clinical Outcome Studies of Schizophrenia

Abstract: BackgroundEndophenotypes are quantitative, laboratory-based measures representing intermediate links in the pathways between genetic variation and the clinical expression of a disorder. Ideal endophenotypes exhibit deficits in patients, are stable over time and across shifts in psychopathology, and are suitable for repeat testing. Unfortunately, many leading candidate endophenotypes in schizophrenia have not been fully characterized simultaneously in large cohorts of patients and controls across these properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
177
2
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(202 citation statements)
references
References 79 publications
(121 reference statements)
15
177
2
7
Order By: Relevance
“…In accordance with clinical EEG observations using a similar sensory gating paradigm (Light et al . 2012), we observed a response suppression of the second pulse ( anova main effect of pulse order, P  < 0.001, F  = 12.61 and P  < 0.001, F  = 11.91 for PCs and interneurones respectively). However, there was no significant difference in sensory gating between genotypes ( P  > 0.05 for both cell types for the anova interaction effect between genotype and pulse number; Fig.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…In accordance with clinical EEG observations using a similar sensory gating paradigm (Light et al . 2012), we observed a response suppression of the second pulse ( anova main effect of pulse order, P  < 0.001, F  = 12.61 and P  < 0.001, F  = 11.91 for PCs and interneurones respectively). However, there was no significant difference in sensory gating between genotypes ( P  > 0.05 for both cell types for the anova interaction effect between genotype and pulse number; Fig.…”
Section: Resultsmentioning
confidence: 69%
“…2007, Light et al . 2012). On a mechanistic level, we found deficient function of putative GABAergic FSIs during pre‐attentive processing of auditory information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has already been demonstrated that in patients with schizophrenia, gating processes do not function properly, and they among other factors are responsible for cognitive deficits. One of the testing methods of the efficiency of gating processes is testing of the so-called auditory evoked potentials [59,60]. So far, various studies have confirmed the irregularity of these processes based on the analysis of the waves P50, P200, N100, N200, P300 in patients and their healthy first-line relatives, which make them potential "candidates" to the name of endophenotypes or markers in schizophrenia [ 59,61,62].…”
Section: Resultsmentioning
confidence: 99%
“…One of the testing methods of the efficiency of gating processes is testing of the so-called auditory evoked potentials [59,60]. So far, various studies have confirmed the irregularity of these processes based on the analysis of the waves P50, P200, N100, N200, P300 in patients and their healthy first-line relatives, which make them potential "candidates" to the name of endophenotypes or markers in schizophrenia [ 59,61,62]. Based on the analysis of auditory evoked potentials researchers conclude that in patients suffering from schizophrenia, there is hyper sensitivity of neurons to stimuli, and hence, reduced initial selection of information occurs [63,64].…”
Section: Resultsmentioning
confidence: 99%